Prevalence of Incidental Prostate Carcinoma among Patients Undergoing Turp for Benign Prostatic Enlargement (Tanzania Medical Journal, 2021)
BackgroundIncidental prostate cancer is detected by histological examination of resected biopsy tissue that has been previously diagnosed as benign. It has the potential for progressing to become a disease necessitating active treatment. There is paucity of data on detection of incidental prostate cancer in Tanzania. A study done in northern Tanzania among the urban public sector revealed an alarming detection rate of 21.71%. We aimed to establish the prevalence of incidental prostate cancer among men surgically treated for benign prostate enlargement with considered normal range of prostate specific antigen. MethodsThis was a retrospective hospital-based cross-sectional study conducted to establish the prevalence of incidental prostate cancer among men who underwent transurethral resection of prostate with considered normal range of prostate-specific antigen from 2010 to 2019 at Aga Khan Hospital Dar es salaam, Tanzania. To find the prevalence of incidental prostate cancer with 95% confidence level, 5% tolerable error, minimum of 195 participants’ data was reviewed, and factors associated with incidental prostate carcinoma were evaluated by binary regression analysis. ResultsTotal of 195 men were included in the study. The prevalence of incidental prostate cancer among men with prostate-specific antigen levels of less than 5.5ng/mL was 7.2% (95% CI, 4.0 to 11.8%). More than half of the patients had high-grade cancer and three quarters had T1b histological subtype making up the clinically significant category. For every 1-year increase in age from age of 65 years, risk of incidental prostate cancer increased by 1.6 (95% CI, 1.054 to 23.38; P<0.05) and for every unit increase in prostate specific antigen, incidental prostate cancer increased by 2.2 (95% CI, 1.953 to 42.28; P<0.05). ConclusionThe Incidental prostate cancer detection rate of 7.2% in our settings is within the range found internationally.